2013
DOI: 10.1001/jama.2013.278040
|View full text |Cite
|
Sign up to set email alerts
|

Menopausal Hormone Therapy and Health Outcomes During the Intervention and Extended Poststopping Phases of the Women’s Health Initiative Randomized Trials

Abstract: IMPORTANCE Menopausal hormone therapy continues in clinical use but questions remain regarding its risks and benefits for chronic disease prevention.OBJECTIVE To report a comprehensive, integrated overview of findings from the 2 Women's Health Initiative (WHI) hormone therapy trials with extended postintervention follow-up. DESIGN, SETTING, AND PARTICIPANTSA total of 27 347 postmenopausal women aged 50 to 79 years were enrolled at 40 US centers. INTERVENTIONS Women with an intact uterus received conjugated eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
1,070
3
80

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 1,291 publications
(1,184 citation statements)
references
References 55 publications
31
1,070
3
80
Order By: Relevance
“…Previous reports showed that among women aged 50 to 59 years at baseline in the overall WHI E‐Alone trial, randomization to E‐Alone versus placebo was associated with lower risk of MI, CHD, and mortality during the trial and in long‐term follow‐up 3. Among women aged 50 to 59 years at baseline in the WHI E‐Alone Trial, the WHI‐CACS showed that randomization to E‐Alone versus placebo resulted in lower odds of CAC measured ≈8.7 years after baseline, independent of CVD risk factors also associated with subsequent CAC 5.…”
Section: Discussionmentioning
confidence: 96%
“…Previous reports showed that among women aged 50 to 59 years at baseline in the overall WHI E‐Alone trial, randomization to E‐Alone versus placebo was associated with lower risk of MI, CHD, and mortality during the trial and in long‐term follow‐up 3. Among women aged 50 to 59 years at baseline in the WHI E‐Alone Trial, the WHI‐CACS showed that randomization to E‐Alone versus placebo resulted in lower odds of CAC measured ≈8.7 years after baseline, independent of CVD risk factors also associated with subsequent CAC 5.…”
Section: Discussionmentioning
confidence: 96%
“…Data to support these conclusions come from multiple sources as reviewed extensively as well as from the a 13-year follow-up of the WHI study (Manson et al 2013). For this reason, the term HRT, which implies that all women should accept this therapy, has been replaced by the term MHT.…”
Section: Oestrogen Therapy and Menopausementioning
confidence: 99%
“…Esta hipóte-sis parece confirmarse en un análisis del Nurses' Health Study, el cual encontró que las mujeres que iniciaron la THM combinada en los primeros 10 años tenían un RR de enfermedad coronaria de 0,72 (IC 95% 0,56 a 0,92), mientras que las que la iniciaron posteriormente tenían un RR de 0,90, (IC 95% 0,62 A 1,29) (27) . Igualmente, el mismo WHI mostró que las mujeres que usaban THM en los primeros 10 años de posmenopausia no tenían aumento del riesgo coronario, mientras que las que iniciaban su uso 20 años después de la menopausia sí tenían un mayor riesgo en 52% (IC 95% 7,0 a 117%) (28) . Aquí se ha planteado el concepto de ventana de oportunidad de la THM; en mujeres menopáusicas recientes, con sistema cardiovascular más sano, la THM sería cardioprotectora, fenómeno más evidente aun en mujeres con insuficiencia ovárica primaria, a diferencia de las mujeres mayores de 60 años, con arterias dañadas y con placas de ateroesclerosis inestables, en quienes sería perjudicial.…”
Section: Enfermedad Cardiovascularunclassified